Water-Use Efficiency of Co-occurring Sky-Island Pine Species in the North American Great Basin - Liu, Xinsheng; Ziaco, Emanuele; Biondi, Franco (Frontiers in Plant Science, 2021)
Water-use efficiency (WUE), weighing the balance between plant transpiration and growth, is a key characteristic of ecosystem functioning and a component of tree drought resistance. Seasonal dynamics of tree-level WUE and its connections with drought variability have not been previously explored in sky-island montane forests. We investigated whole-tree transpiration and stem growth of bristlecone (Pinus longaeva) and limber pine (Pinus flexilis) within a high-elevation stand in central-eastern Nevada, USA, using sub-hourly measurements over five years (2013–2017). A moderate drought was generally observed early in the growing season, whereas interannual variability of summer rains determined drought levels between years, i.e., reducing drought stress in 2013–2014 while enhancing it in 2015–2017. Transpiration and basal area increment (BAI) of both pines were coupled throughout June–July, resulting in a high but relatively constant early-season WUE. In contrast, both pines showed high interannual plasticity in late-season WUE, with a predominant role of stem growth in driving WUE. Overall, bristlecone pine was characterized by a lower WUE compared to limber pine. Dry or wet episodes in the late growing season overrode species differences. Our results suggested thresholds of vapor pressure deficit and soil moisture that would lead to opposite responses of WUE to late-season dry or wet conditions. These findings provide novel insights and clarify potential mechanisms modulating tree-level WUE in sky-island ecosystems of semi-arid regions, thereby helping land managers to design appropriate science-based strategies and reduce uncertainties associated with the impact of future climatic changes.